Effects of Watercress (Nasturtium nasturtium) extract on selected immunological parameters of rainbow trout (Oncorhynchus mykiss) - K. Ahmadi; M. Banaee; M.A. Nematollahi; A.R. Mirvaghefei; M.S. Asadi (Open Veterinary Journal, 2012)
Watercress (Nasturtium nasturtium) is a medical plant containing diverse chemically-active substances with biological properties. The present study was conducted to investigate the immunomodulatory effects of watercress extract on immunological and hematological parameters of rainbow trout (Oncorhynchus mykiss). Fish were fed for 21 days with diet supplemented with 0.1% and 1% of watercress extract per 1 kg food and with a normal diet as control. Hematological parameters such as red blood cells (RBC) and white blood cells (WBC), hematocrit (Hct), hemoglobin (Hb), RBC index like mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC) as well as immunological parameters such as peroxidase, lysozyme and complement activities, total protein, albumin and globulin levels were measured after 21 days of watercress extract treatment. The results indicated that oral administration of 1 % watercress extract in fish may enhance some hematological and immunological parameters including Hb and MCHC, lysozyme and complement activities, total protein and globulin levels, compared to the controls after 21 days of experimental period. In conclusion, on the basis of these results, oral administration of watercress extract may be useful to improve fish’s immune system.